Responses of Megathyrsus maximus accessions under shaded conditions - Mayorga, Mildred; Cardoso, Juan Andrés (International Center for Tropical Agriculture, 2023)
Megathyrsus maximus is a species widely used as forage in livestock systems due to its high yield, good nutritional quality, and easy propagation. Knowing the response of the genetic diversity of the species to growth under shade is important to determine its potential use in silvopastoral systems, which are a sustainable alternative to mitigate the negative impacts of forage production in monoculture systems on soil health, animal welfare and the environment. To evaluate the response of M. maximus genotypes to shade conditions, 33 genotypes were planted in two conditions, without shade and with 75% shade. The response was evaluated in gas exchange, chlorophyll fluorescence, SPAD index, stem length, biomass partitioning, leaf area, number of leaves and specific leaf area. Under shade conditions, plants showed lower stomatal conductance, lower transpiration, higher photochemical efficiency of PSII operation, higher leaf area, lower number of leaves, lower root: shoot ratio, higher specific leaf area, higher SPAD index and higher stem length. The genotypes that showed the greatest phenotypic plasticity to adapt to the shade condition were CIAT16021, CIAT6299, CIAT6868 and CIAT16060.